Assessment of catalytic thermal hydrolysis of swine manure slurry as liquid fertilizer: Insights into nutrients and metals - Xie, Shiyu; Zhang, Tao; Mishra, Anshuman; Tiwari, Ashutosh; Bolan, Nanthi S. (Frontiers in Environmental Science, 2022)
The recovery of nutrients from livestock manure has generated a lot of interest in biosolids value-adding. There is now more research on manure with high solids content but less study on manure with lower solids content. This study used swine manure slurry as the research object and comprehensively examined the characteristics of organic matter conversion, nitrogen, phosphorus, and metals release during the catalytic-thermal hydrolysis (TH) process. It was found that ammonia nitrogen showed a continuous increase with increasing temperature while inorganic phosphorus showed a rising and then decreasing trend. The addition of HCl and H2O2 (TH-HCl-H2O2) promoted the hydrolysis of organic matter, showing the best nitrogen and phosphorus release performance, releasing 62.2% of inorganic phosphorus and 50.8% of nitrogen. The release characteristics of nutrients and metals from the TH process were significantly affected by the addition of HCl and H2O2, according to structural equation modelling study. The data analysis demonstrated that the liquid fertilizer produced by TH did not surpass the environmental risk associated with nutrients or the ecological risk associated with heavy metals. This study would offer theoretical justification for biowaste conversion for agricultural applications.